Peningkatan Usaha Melalui Diversifikasi Kain Belah Ketupat Di Umkm Quenshaa Tanggamus - Cahyani Pratisti; Anandha Sartika Putri; Lani Oktasari (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
One of the handicrafts from Lampung Province that is not widely known is kain belah ketupat. This community service activity aims to introduce kain belah ketupat which are the superior characteristics of Lampung Province and increase their selling value so they can compete in national and global markets. Service activities carried out using a Participatory Learning and Action (PLA) approach with lecture, discussion, and training methods. After the training, new products were obtained in the form of sling bags, tissue boxes, scarves, laptop bags and masks. MSMEs also now have logos, new packaging, as well as business Instagram, blogs, and Shopee. Perhaps after this service, the sales of MSMEs would continue to increase so that they can globalize Lampung's typical kain belah ketupat products.